Konjac glucomannan as an emerging nutritional strategy for obesity control via gut microbiota and metabolic regulation - Anindita Ghosh; Priyanka Mohol; Sumana Ghosh (Discover Food)
Abstract Purpose This review aims to evaluate the role of Konjac Glucomannan (KGM) as an emerging nutritional strategy in regulating obesity and metabolic dysfunction through its influences on weight regulation, various metabolic biomarkers and intestinal microbiota composition. Methods A systematic search was conducted 10 randomised controlled trials and 9 review articles between 2014 and 2024 across five scientific databases. Studies assessing the impact of KGM on BMI, weight loss, lipid metabolism, glycemic control, and gut microbiota composition were included. Key outcomes were extracted, standardized and statistically analysed using RStudio with descriptive and correlational analyses for consistency across different intervention protocols. Results KGM supplementation (≥ 5 g/day for ≥ 12 weeks) is frequently associated with reductions in BMI (mean:1.49 kg/m2), weight (mean:3.18 kg), and waist circumference (mean:2.11 cm) of overweight and obese individuals. The metabolism underwent considerable changes, in particular, as a result of a calorie-restricted diet or the inclusion of probiotics in the diet. KGM altered the gut microbiota by enriching Bacteroidetes, Akkermansia, and Bifidobacterium and decreasing Clostridia and Proteobacteria, indicating a possible metabolic control microbiome-wise. An increased synthesis of short chain fatty acids namely propionate and butyrate interrelated with a diminution in low density lipoprotein (LDL) levels and inflammatory markers like C-reactive protein (CRP) and interleukin-6 (IL-6).A comparative analysis of KGM with the other soluble dietary fibers psyllium and inulin disclosed its unique properties (viscosity, satiety-inducing and SCFA profile) justifying the significant gut-microbial and metabolic changes observed on KGM supplementation in overweight and obese individuals. Conclusion KGM emerges as a promising functional dietary component in regulating obesity and metabolic syndrome, with its effects attributed to both its physicochemical properties and its influences on gut-microbial dynamics. Nevertheless, well designed large-scale longitudinal studies using multi-omics and precision nutrition approaches are required to determine standardised dosing regimens, optimise synergistic dietary interventions, and to increase the clinical viability of KGM administration as an emerging, preventive and nutritional strategy in obesity management.